Comparative Study of Aquifer Characteristics and Ground Water Potential of Dun Valley and Terai Area: Case Study from Dang Valley and Kapilvastu Area - Pandey, Dharma Raj; Panthee, Suman; Ghimire, Prativa (Journal of Nepal Hydrogeological Association, 2025)
This study compares aquifer characteristics in the Dang Valley and Kapilvastu area using litholog and pumping test data. It analyzed 20 lithologs and pumping tests from Dang and 27 from Kapilvastu. Subsurface formations were interpreted from lithologs, and key aquifer parameters were calculated using the Jacob method. The study found that Dang Valley and Kapilvastu share different subsurface formations, with groundwater typically occurring below the third or fourth layer. Pumping test analysis provided key aquifer parameters, including transmissivity, hydraulic conductivity, and specific capacity. The results show that the average transmissivity in Dang Valley is 2689.84 m²/ day, while in the Kapilvastu area it is 2296.58 m²/day, indicating that most of the aquifer in Dang Valley has a consistent capacity to transmit groundwater as compared to Kapilvastu areas, but highest transmissibility obtained in Valwad Kapilvastu (7120 m²/day). Similarly, the average hydraulic conductivity is higher in Kapilvastu (246.87 m/day) compared to Dang Valley (123.32 m/day), suggesting that the aquifer materials in Kapilvastu allow water to move more freely. The specific capacity is greater in Kapilvastu (229.71 m³/day) than in Dang valley (194.72 m³/day). The Dun Valley experienced a greater decrease in water levels compared to the Terai, with an average drawdown of 18.43 meters and a maximum drawdown of 37 meters. Overall, these comparisons show that the central part of the Dang Valley including Dharna, Guruwagaun, Goltakuri, and Gairtilawari as well as in the northeastern part of Kapilvastu such as Bhaluwad, Mormi, Banganga, Nibuwa, and Gorusinge, the aquifer characteristics were found to be similar, indicating areas with good groundwater potential. In contrast, the peripheral areas of the Dang Valley and the southeastern part of Kapilvastu including Fattepur, Purnihawa, and Semari as well as the western areas such as Jawabhari, Birpur, and Turuntapur, have aquifers that showed relatively poor groundwater potential, which is likely due to differences in the depositional environment and the nature of the sediments.